Efektivitas Terapi Musik Klasik dalam Menurunkan Kecemasan Pada Ibu Dengan Komplikasi Kehamilan di RS Islam Jakarta Cempaka Putih - Anggra Hamidah; Siti Rochanah; Lela Larasati (Jurnal Sains dan Ilmu Terapan, 2026)
Pregnancy complications such as preeclampsia, bleeding, and infection can endanger maternal and fetal health and increase anxiety in pregnant women. Unmanaged anxiety may negatively affect physical and psychological well-being and pregnancy outcomes. Classical music therapy is a non-pharmacological intervention known to promote relaxation and reduce anxiety. This study aimed to determine the effectiveness of classical music therapy in reducing anxiety among pregnant women with pregnancy complications at Jakarta Islamic Hospital Cempaka Putih. A quasi-experimental study with a one-group pretest–posttest design was conducted involving 30 pregnant women selected through purposive sampling. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after 15–20 minutes of classical music therapy per session. Data were analyzed using a paired sample t-test. The results showed a significant decrease in mean anxiety scores from 23.67 (moderate–severe) to 9.47 (mild) after the intervention (p < 0.001). In conclusion, classical music therapy is effective in reducing anxiety among pregnant women with pregnancy complications and is recommended as a supportive intervention in antenatal care.